The Self-Confidence of UKM Perisai Diri Pencak Silat Athletes at UPI in Facing Competitions as Seen From Their Level Of Anxiety - Fikri Zulfikar Najat; Tono Haryono; Unun Umaran (Universitas Negeri Semarang, 2026)
Background: Pencak silat is a competitive martial art originating from Indonesia that relies not only on physical strength and technique but also requires intense focus and concentration. Athletes often face immense pressure, and an inability to control their emotions can lead to a decrease in their performance. Objectives: This study aims to empirically analyze the relationship between cognitive anxiety and somatic anxiety and self-confidence among athletes in the UKM Perisai Diri UPI, particularly those facing the “double burden” of academic and athletic demands. Method: This study employed a quantitative, descriptive-correlational design; data were collected using the CSAI-2R questionnaire. Given that the data distribution was not normal (P < 0.05), Spearman’s rank correlation ( s) was used as the primary analysis. Result: The results showed a very strong and significant negative correlation, including cognitive anxiety and athlete self-confidence ( s = -0.938; < 0.01), somatic anxiety and self-confidence ( s = -0.882; < 0.01). In addition, as many as 63.4% of athletes had high self-confidence, 53.3% managed to control mental anxiety. However, simultaneously, the remaining 26.7% experienced high levels of somatic anxiety (average score 26.17). Conclusion: The strong and significant correlation between the level of anxiety and self-confidence among UPI Perisai Diri UKM athletes indicates that the mental condition of the athletes is very sensitive to competitive stress, even though they have a high level of self-confidence.